Conversion from Roux-En-Y Gastric Bypass to Sadi-S, with a Gastro-Gastric Jejunal Bridge as a Treatment of Obesity Recidivism: Case Report - Dib, V (2022)
There is a considerable weight regain after the Roux-en-Y gastric bypass (RYGB) surgery. Surgical conversion to more powerful metabolic techniques, like one anastomosis duodenal switch with sleeve gastrectomy (SADI-S), can be effective in this scenario, but surgically challenging. This case report aims to demonstrate technical modifications that simplifies the conversion of Roux-en-Y gastric bypass to SADI-S, in one stage. Female patient submitted to laparoscopic RYGB 10 years before with nadir of 29,47Kg/m². In the last 4 years, she had regained weight, reaching a body mass index of 46,48Kg/m². Surgical conversion was done laparoscopically, preserving the gastrojejunal anastomosis from the previous RYGB and the proximal 8cm of jejunal alimentary limb, which was transected at this level and used as a bridge between gastric pouch and antrum. Previously, the fundus, gastric body and part of the antrum were removed. The remaining alimentary limb, the gallbladder and the candy cane was removed. This was a single stage procedure, without complications. The interposition of the proximal alimentary limb of gastric bypass, between gastric pouch and antrum, has shown to be safe and feasible in RYGB conversion to SADI-S. The removal of the remnant alimentary limb makes the procedure shorter.